Adventure education: Redux*. Issue 4 (2nd October 2017) - Brown, Mike; Beames, Simon
ABSTRACT: This article discusses the meanings of adventure and its role in learning. An analysis of literature from the fields of education, recreation and tourism suggests that definitions of adventure are constantly undergoing reinterpretation. We highlight how 'narrow' views of adventure, which appeal to notions of risk and danger, are paradoxically shaped by control and predictability. A focus on activities involving risk and danger limit the pedagogical potential of adventure. We argue that current forms of adventure education practice fail to meet the needs of learners who are confronting a world of change, unpredictability and complexity. To better understand the broader social and educational landscape, we briefly outline some features of late modernity that require learners to cope with uncertainty in their everyday lives. We suggest an alternative approach to adventurous learning that embraces features of late modernity and takes as its starting point the everyday life of the learner.